BUILDING TEACHER DISCIPLINE THROUGH ANALYSIS OF ORGANIZATIONAL CULTURE AND MOTIVATION (Case Study at SMK Mitra Karya Karawang) - Muh, Rajab; Munawar N.A. (Dinasti International Journal of Management Science, 2020)
This study aims to analyze the influence of organizational culture, and work motivation towards discipline work at SMK Mitra Karya Karawang. The primary data were derived from questionnaires and the secondary data were from school statistics. The population of the research was all college teachers in SMK Mitra Karya Karawang. The research method is: quantitative research that uses the survey method in question is to explain the causal influence or correlation which is commonly referred to as path analysis with the data analysis technique used in this research is SEM (structural equation modeling) lisrel 8.8. The respondents were 150 teachers of Mitra Karya Karawang Vocational School with a minimum service period of 1 year. The results show that organizational culture, anda work motivation together have a significant effect on work discipline. Partially organizational culture and work motivation have a significant positive effect on work discipline. The most work motivation is a powerful variable of influence on discipline work.